Active teaching methodologies in health education - Luciana Faria SANGLARD; Luciana Butini OLIVEIRA; Rui Barbosa de BRITO JUNIOR; Marcela Cristina Manfré de CALASANS; Lorenna Fernandes Das Chagas Carvalho SIMÕES; Yara Silvia Marques de Melo ISSA; Rosangela Dantas FRATESCHI (Faculdade São Leopoldo Mandic, 2022)
ABSTRACT This study is a literature review on the contributions of active methodologies in Higher Education in the health area. From the reviewed literature (texts, articles and books), an academic essay was written, addressing ideas, reflections, literature citations and authors' personal impressions on the theme. After analyzing the literature, it was realized that active methodologies despite being involved in the teaching-learning process for several years, still require that teachers and students widely appropriate their benefits. The implementation of this change will help in coping with the factors that have negatively interfered in higher health education. It is a challenge that needs to be embraced by teachers and students. Conclusions: Active teaching methodologies can be included in all teaching models and methods and aim to promote learning and expand the possibilities for students to develop their competencies.